Kupffer Cell Inactivation Alters Endothelial Cell Adhesion Molecules in Cecal Ligation and Puncture-Induced Sepsis - Sumeet Manandhar; Ravinder Reddy Gaddam; Stephen Chambers; Madhav Bhatia (Biomolecules, 2024)
The activation of Kupffer cells, resident macrophages in the liver, is closely associated with the inflammatory response during sepsis, which leads to multiple-organ failure. However, how Kupffer cell activation affects adhesion molecules (ICAM-1 and VCAM-1) in sepsis has not been determined. This study investigated Kupffer cell inactivation’s (by gadolinium chloride; GdCl3) effects on adhesion molecule expression in CLP-induced sepsis. The induction of sepsis resulted in increased expression of liver and lung ICAM-1 and VCAM-1. GdCl3 pretreatment significantly decreased liver ICAM-1 expression but had no effect on VCAM-1 expression. In contrast, GdCl3 pretreatment had no effect on sepsis-induced increased adhesion molecule expression in the lungs. Similarly, the immunoreactivity of ICAM-1 was decreased in liver sinusoidal endothelial cells but increased in pulmonary endothelial cells in septic mice pretreated with GdCl3. Further, GdCl3 pretreatment had no effect on the immunoreactivity of VCAM-1 in endothelial cells of the liver and lungs. Hence, the findings of this study demonstrate the differential effects of Kupffer cell inactivation on liver and lung adhesion molecules and suggest the complexity of their involvement in the pathophysiology of sepsis.